An innovative magnetic bar separator for removal of chromium ions in tanning wastewater. (April 2021) - Li, Tao; Yang, Tianlei; Yu, Zhenyu; Xu, Guoli; Du, Meiling; Guan, Yueping; Guo, Chen
Highlights: An innovative in-situ cleaning magnetic separator was designed and manufactured. The capture efficiency of 15nm Fe3 O4 nanoparticles by the Nd-Fe-B separator is 99.8 %. Modified Fe3 O4 nanoparticle is effective for Cr removal from tanning wastewater. Modified Fe3 O4 magnetic separation remove Cr in tannery wastewater is low cost. Modified Fe3 O4 particles can be recycled, and chromium can be retrieved. Abstract: An innovative magnetic separator was designed to capture chromium ions in tanning wastewater through magnetic nanoparticles. The effect of Fe3 O4 magnetic particle concentrations, magnetic bar spacing and liquid flow velocities on the capture efficiency of the magnetic separator on magnetic nanoparticles in a simulated system was investigated. When the concentration of the magnetic particles is less than 400mg/L, the flow velocity is lower than 18L/hr, and the spacing of the magnetic bar is less than 30mm, the capture efficiency of Fe3 O4 magnetic nanoparticles could keep more than 99.4 % within 3h. The magnetic separator was applied to treat chromium-containing tanning wastewater. The initial chromium concentration of the wastewater is 127mg/L. The capture efficiency could keep 99.7 % during 5 h, the wastewater treatment capacity is 18 L/hr and the outlet Cr<0.5mg/L. Amino Fe3 O4 can be regenerated and reused 9 times, the chromium capture rate is above 99.6 %, and the outlet Cr<0.5mg/L. The magnetic separator is suitable for large-scale heavy metal wastewater treatment.